2010
DOI: 10.1002/art.27430
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutamate/glutamine compounds in the brains of patients with fibromyalgia: A magnetic resonance spectroscopy study

Abstract: Objective. Fibromyalgia (FM) has been defined as a systemic disorder that is clinically characterized by pain, cognitive deficit, and the presence of associated psychopathology, all of which are suggestive of a primary brain dysfunction. This study was undertaken to identify the nature of this cerebral dysfunction by assessing the brain metabolite patterns in patients with FM through magnetic resonance spectroscopy (MRS) techniques.Methods. A cohort of 28 female patients with FM and a control group of 24 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 22 publications
7
70
2
1
Order By: Relevance
“…[10][11][12][13] Although there were no differences between patients and controls at this level, we found a strong significant positive correlation between Glu/Cr levels in the left thalamus and the VAS (r ϭ 0.730, P ϭ .007). This result strengthens a recently published MRS study, 26 in which patients with more pain (high VAS score) showed higher Glx levels in the left thalamus, though without significant correlation. Our result could reflect the role of the thalamic structures in the processing of pain signal intensity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[10][11][12][13] Although there were no differences between patients and controls at this level, we found a strong significant positive correlation between Glu/Cr levels in the left thalamus and the VAS (r ϭ 0.730, P ϭ .007). This result strengthens a recently published MRS study, 26 in which patients with more pain (high VAS score) showed higher Glx levels in the left thalamus, though without significant correlation. Our result could reflect the role of the thalamic structures in the processing of pain signal intensity.…”
Section: Discussionsupporting
confidence: 90%
“…Our result could reflect the role of the thalamic structures in the processing of pain signal intensity. However, both in our study and in the previous MRS studies 26,27 that explored this region, no differences between patients and HC were found in metabolites and their ratios, even though alterations of CBF are well documented at this level. In our opinion, this information suggests that the thalamus is not primarily involved in this disorder but probably interacts with other cognitive areas that process pain such as the VLPFC.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Human MRS studies have identified increased inositol in medial temporal lobe including amygdala (Venkatraman et al, 2009) and in fronto-cortical (PFC, ACC) gray and white matter (Caetano et al, 2005;Kumar et al, 2002) in depression, and in amygdala and thalamus in association with high depression symptoms in fibromyalgia (Valdes et al, 2010); decreased PFC-ACC inositol has also been reported in depression (Coupland et al, 2005). Inositol is an intracellular lipid and precursor of phosphatidylinositol (PI) structural lipids and inositol phosphate secondary messengers e.g.…”
Section: Metabolic and Structural Changes In Cps Micementioning
confidence: 99%